State tax and expenditure limitations and supermajority requirements: New and updated data - Cody Kallen (American Enterprise Institute (AEI), 2017)
This paper presents original primary-source research on state-level tax and expenditure limitations and supermajority requirements to raise taxes.
Keywords: A; 330; tax reform; State taxes